Pengaruh Pengalaman Kerja Dan Kompetensi Auditor Terhadap Kualitas Hasil Pemeriksaan (Studi Kasus pada Kantor BPKP Bandar Lampung.) - Yunus Fiscal; Justian Suhendra; Riswan RISWAN (Jurnal Akuntansi dan Keuangan, 2012)
The purpose of this research is to analyze the influence of work experience and the competence of the auditor with respect to quality of result of inspection. This study uses qualitative methods of data analysis and kuntitiatif. Based on the results of research and analysis on the existing problems, then it can be concluded that the work experience and the competence of the auditors positive and significant effect on the quality of result of inspection. We recommend that the auditor should have the experience, education and training programs to audit, so that in their performance audit Auditors can accomplish the task with good quality, supported by its individual capabilities